Capital Structure and Firm Efficiency of Non Financial Institutions in Nepal (Journal of Nepalese Business Studies, 2019)
Capital structure and firm’s efficiency of non-financial companies of Nepal is a less explored research in the Nepalese context. The paper examines the relationship between leverage and efficiency of non-financial firms in Nepal. This paper employs descriptive as well as casual research design to examine the general structure of leverage and efficiency and their relationship too. Secondary data were employed for the study which was extracted from the annual report of respective companies with 60 observations ranging from two to 14 years. The non-financial institution listed in Nepal Stock Exchange is the population of the study. Fifteen companies representing one from trading, three from the hotel sector, five from manufacturing, six from hydro were selected as the sample for the study employing stratified cum purposive sampling method. The variables namely size, tangibility, growth, profitability, leverage and efficiency were analyzed. Descriptive as well as regression analysis was used to assess the relationship among the variables. Different models were used to test the hypothesis. Most of the Nepalese non-financial institution employs both debt and equity in their capital formation. The firms having high leverage are less efficient and more efficient firms’ use low leverage. Nepalese non-financial institutions increase in size, investment intangible assets and profitability does not necessarily increase the efficiency of the firms. The positive relationship between efficiency and tangibility justify that more investment in tangible assets increases the firm’s efficiency. An increase in sales increases the growth rate of nonfinancial firms as suggested by the positive relationship between size and growth. There is no consistency on the impact of size, tangibility, profitability, and growth on leverage among four industries within nonfinancial firms. The major conclusion of this study is that size, tangibility, profitability, and growth are the significant factors in determining the efficiency and leverage of Nepalese non-financial firms. The firms having high leverage are less efficient and more efficient firms use low leverage.